The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/eye.2008.284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid action of oestradiol against hydrogen peroxide-induced oxidative stress in cataractous lens epithelium: an in vitro study

Abstract: Purpose To evaluate the short-term protective effects of oestradiol against damages because of oxidative stress in human lens epithelial cells (LECs). Methods The central zone of human lens epithelium was obtained from the cataract surgery and cultured in MEM culture medium. These cultured LECs were treated with 17b-oestradiol for varying time intervals from 1 to 5 min followed by treatment with H 2 O 2 (5 Â 10 À6 M) in the culture medium. Catalase activity was measured to access the oxidative stress levels. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Gottipati and Cammarata reported that 17 b-estradiol protects human lens epithelial cells against oxidative stress via increasing the activity of mitochondrial superoxide dismutase [30]. A recent study by Gajjar et al demonstrated the protective effect of estradiol against hydrogen peroxide-induced oxidative stress in lens epithelium cells [31].…”
Section: Discussionmentioning
confidence: 97%
“…Gottipati and Cammarata reported that 17 b-estradiol protects human lens epithelial cells against oxidative stress via increasing the activity of mitochondrial superoxide dismutase [30]. A recent study by Gajjar et al demonstrated the protective effect of estradiol against hydrogen peroxide-induced oxidative stress in lens epithelium cells [31].…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have supported the intracellular and intercellular signaling function of H 2 O 2 [14,15]. The synthesis of catalase in LECs was reported to be dependent on the concentration of H 2 O 2 [16]. It was also reported that H 2 O 2 activates the expression of glutathione peroxidase, an inactivator of H 2 O 2 [17].…”
Section: Discussionmentioning
confidence: 99%
“…Once the removal anterior capsule is removed, the sample was instantly kept in an Essential Medium (containing 10% fetal bovine serum) and immediately transferred to the Research laboratory. A single rhexis for preservation was kept in Minimal Essential Medium, containing 10% fetal bovine serum, and incubated in an incubator containing 5% carbon dioxide at 37°C [11]. The maximum time-lapse from the collection of the sample to the process was 15-20 min.…”
Section: Detailed Examination Of Senile Cataract Patientsmentioning
confidence: 99%